A Skin‐Mountable Hyperthermia Patch Based on Metal Nanofiber Network with High Transparency and Low Resistivity toward Subcutaneous Tumor Treatment (Adv. Funct. Mater. 21/2022). (19th May 2022) - Wang, Qi; Sheng, Hongwei; Lv, Yurong; Liang, Jie; Liu, Yan; Li, Na; Xie, Erqing; Su, Qing; Ershad, Faheem; Lan, Wei; Wang, Jing; Yu, Cunjiang
Abstract : Skin‐Mountable Hyperthermia Patch In article number 2111228, Wei Lan, Jing Wang, Cunjiang Yu, and co‐workers fabricate a soft, skin‐mountable, hyperthermia patch (HTP)‐based unidirectional metalized silver nanofibers network that combines high transparency and excellent electrothermal properties. The HTP allows to monitor skin irritation during hyperthermia treatment of subcutaneous tumors and other medical issues.